Identifying the binding mechanism of LEAP2 to receptor GHSR1a. (9th February 2019) - Wang, Jia‐Hui; Li, Hao‐Zheng; Shao, Xiao‐Xia; Nie, Wei‐Han; Liu, Ya‐Li; Xu, Zeng‐Guang; Guo, Zhan‐Yun
Abstract : Liver‐expressed antimicrobial peptide 2 (LEAP2) is a highly conserved secretory peptide first isolated in 2003. However, its exact biological functions remained elusive until a recent study identified it as an endogenous antagonist for the growth hormone secretagogue receptor (GHSR1a), a G protein‐coupled receptor for which the gastric peptide ghrelin is the endogenous agonist. By tuning the ghrelin–GHSR1a system, LEAP2 has an important function in energy metabolism. In the present study, we first demonstrated that LEAP2 and ghrelin actually bound to GHSR1a in a competitive manner, rather than in a non‐competitive manner as previously reported, by binding assays and activation assays. Subsequently, we demonstrated that the antagonistic function of LEAP2 was drastically affected by the manner of its addition. LEAP2 primarily affected the maximal activation effect when added before ghrelin, whereas it primarily affected half‐maximal effective concentration when added at the same time as ghrelin. Thus, LEAP2 behaved as a competitive antagonist if added at the same time as the agonist and a non‐competitive antagonist if added before the agonist. This unusual property of LEAP2 might be caused by its slow dissociation from receptor GHSR1a. We also found that the N‐terminal fragment of LEAP2 was important for receptor binding. Our present study revealed an antagonistic mechanism for LEAP2, and will facilitate the design of novel antagonists for receptor GHSR1a in future studies. Abstract : Using binding assays, we demonstrated liver‐expressed antimicrobial peptide 2 (LEAP2) was a competitive antagonist for ghrelin receptor GHSR1a. However, the manner of addition affected LEAP2's function in activation assays: it behaved as a competitive antagonist when added at the same time as ghrelin, whereas it behaved as a non‐competitive antagonist when added before ghrelin. Its slow dissociation from GHSR1a might cause this unusual property. This study provides new insights into LEAP2's tuning of the ghrelin–GHSR1a system.